2021
DOI: 10.3390/educsci11030114
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Indigenous Science to Identify Contents and Contexts for Science Learning in Order to Promote Education for Sustainable Development

Abstract: Indigenous science is comprised of the science-related knowledge and associated practices of indigenous cultures. Indigenous science provides rich contexts that can contribute to understanding the relationship of sociocultural life and environmental ethics in certain communities. It can also lead to better reflection upon Western modern views of science. Based on a qualitative analysis of indigenous science in the Baduy community (Indonesia), we describe how indigenous science can provide relevant contexts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Other research has demonstrated an increase in students' knowledge of sustainability following the use of innovative programs on this subject [51]. The children acquired content on the protection of the environment and recycling based on the 4R activities; for a better future for all, it is vital that young students learn scientific concepts and recognize the value of promoting sustainability [21]. Recycling has become a reasonably well-developed civic habit but the economic capital and energy needed to transport and transform waste into recyclable material has declined worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has demonstrated an increase in students' knowledge of sustainability following the use of innovative programs on this subject [51]. The children acquired content on the protection of the environment and recycling based on the 4R activities; for a better future for all, it is vital that young students learn scientific concepts and recognize the value of promoting sustainability [21]. Recycling has become a reasonably well-developed civic habit but the economic capital and energy needed to transport and transform waste into recyclable material has declined worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Primary school education is exactly the right time to boost children's development of responsible behaviors towards protection of the environment [19]. However, there are several barriers to overcome in order for students to internalize the concepts of sustainability, such as the lack of awareness or finance for supporting sustainable actions [20,21].…”
Section: Environmental Education Digital Literacy and Gamificationmentioning
confidence: 99%
“…They suggested in workshop discussions that there should be a course on local biodiversity, to gain practical experience and relate scientific knowledge to LEK. Zidny et al (2021) stated that indigenous science can provide relevant contexts for students to learn scientific concepts, as well as help them to recognize the value of promoting sustainability. Screening of the existing curriculum materials indicated that food and environmental education does not complement LEK on local biodiversity.…”
Section: Locals' Perceptions Of Existing Educational Opportunitiesmentioning
confidence: 99%
“…Table 1 shows that there has been a lot of exploration of local wisdom. This is of course implemented in the world of education by having excellent validity, reliability, and practicality (Effendi, 2019;Suardi & Syarifuddin, 2018;Sumardi & Wahyudiati, 2021;Sundari et al, 2021;Szymkowiak et al, 2021;Widyaningrum, 2018;Zidny et al, 2021).…”
Section: Based On Objectives Researchmentioning
confidence: 99%